Evaluación de uso de un cluster oportunista basados en sistemas operativos heterogéneos y HTCondor (2016)
In the technological university of Bolivar, there is a high demand on machines to handle a huge amount of data, in order to process that workload, It uses a grid system, a cluster to provide an infrastructure support to handle that work. To achieve this goal implements the use of HTCondor, a software to control the jobs assigned to this cluster, allowing to perform different tasks, follow the job process, define architecture, even a operative system for the job execution. We test the performance of HTCondor over different operative system, looking for deploy the optimal solution to each tasks, we are building a grid system that can solve any type of task, using the resources we have. To make the most of this resources, we use an opportunistic cluster with heterogeneous operative system, this allow us use a machine if is idle or if the use of that machine is lower that a specific limit. using this we can test the use and performance of tool HTCondor on the different machine and architectures available.. . .